Does Constitutional Court Decision No. 90/PUU-XXI/2023 Violate the Nemo Judex in Causa Sua Principle? - Della Hervi Syahputri; Ampuan Simatupang; Lu Sudirman (Universitas Internasional Batam, 2025)
This study addresses the problem of potential violations of the nemo judex in causa sua principle in Constitutional Court Decision No. 90/PUU-XXI/2023 and their implications for judicial integrity and public trust in Indonesia’s constitutional system. The objective of this research is to analyze the application of the nemo judex in causa sua principle in the decision and to examine its impact on public confidence in the Constitutional Court, particularly in electoral judicial review cases. This study employs a normative juridical method using statutory, conceptual, and case approaches, supported by qualitative analysis of legal materials, judicial decisions, and academic literature. The findings reveal that although the principle of nemo judex in causa sua is normatively recognized in Indonesian law, its implementation remains insufficiently regulated, thereby creating opportunities for conflicts of interest within judicial processes. The analysis of Decision No. 90/PUU-XXI/2023 indicates indications of compromised judicial impartiality, which triggered widespread public criticism and contributed to a decline in institutional credibility. Empirical data further demonstrate fluctuations in public trust, suggesting that controversial decisions perceived as biased can significantly weaken democratic legitimacy, while decisions aligned with fairness and constitutional values tend to restore public confidence. This study highlights the urgent need for institutional reform, including the formalization of recusal mechanisms, stricter enforcement of judicial ethics, and enhanced transparency and accountability in judicial proceedings.